1877 Mo. Laws 240, An Act to preserve the public peace by preventing the display of knives and other deadly weapons in the presence of one or more persons, § 1 - (:unkn) unknown (General Publisher, 1877)
Prohibited the brandishing, in a rude angry, or threatening manner, any firearms, Bowie-knife, dirk, dagger, slung-shot, or other deadly weapon. Violators guilty of a misdemeanor, fined not lesss than ten but no more than five hundred dollars, or imprisoned not exceeding six months, or both.
--
Keywords: BRANDISHING